Lone mothers and paid work : a thesis submitted in partial fulfillment of the requirements for the degree of Master of Arts in Social Policy at Massey University - Morris, Leonie (Massey University, 1999)
In recent years in New Zealand the Government's policy of coercing lone mothers on the Domestic Purposes Benefit (DPB) into paid work has been intensified. This thesis examines this policy and focuses on the following issues: what assists/impedes paid work for lone mothers, what policy measures are employed to facilitate and/or coerce DPB recipients into paid work, and how effective are these measures? Three research methods were used: • a comparative study of government policy towards lone mothers and their workforce participation in Sweden, the United States of America, Australia, and New Zealand; • a qualitative study of six women on the DPB to provide illustrations from lone mothers' perspectives; • analysis of material obtained under the Official Information Act to examine the assumptions behind government policy decisions on lone mothers. All findings confirmed that women on the DPB face a formidable number of barriers and obstacles to entering paid work. The principal issues were: • the lack of availability of suitable jobs; • the low level of the wages for jobs available to lone mothers; and • the lack of government provisions designed to help lone mothers reconcile their dual responsibilities as breadwinner and principal caregiver. In both Sweden and the United States lone mothers are expected to be in paid work, and in both countries lone mothers have high workforce participation. However, these countries pursue diametrically opposed policies. In Sweden an active labour market policy and extensive welfare programmmes support parents to combine parenting with employment. In the United States little support is provided, and if lone mothers cannot find work in the private sector they are often obliged to go on a workfare programme. The disadvantages to this approach are that many lone mothers in paid work still live in poverty, and they have a very high rate of leaving work and returning to the benefit because of the lack of support for them in the workforce. There is a danger that if New Zealand continues to follow the United States' policies, the same negative outcomes will predominate here.
Keywords: Domestic Purposes Benefit; Working mothers; Unmarried mothers; New Zealand; Employment